2021
DOI: 10.3390/ijerph181910114
|View full text |Cite
|
Sign up to set email alerts
|

Human–Animal Interaction and Perinatal Mental Health: A Narrative Review of Selected Literature and Call for Research

Abstract: There is a paucity of research exploring how relationships with household pets may impact maternal mental health. We are unaware of any study to date that has examined associations between individuals’ relationships with their pets and psychological adjustment in the perinatal period. Using a biobehavioral lens, this paper provides a narrative overview of the literature on perinatal mental health and human–animal interaction (HAI). We focus on the role of social relationships, stress, and stress reduction in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 268 publications
(336 reference statements)
0
1
0
Order By: Relevance
“…These forms of childhood adversity typically involve less perceived threats when compared to direct forms of victimization, such as exposure to intimate partner violence or physical abuse. Indeed, positive human–animal interactions are hypothesized to promote wellbeing by buffering stress both prior to and after activation of the stress response system [ 45 , 46 ] and by providing socioemotional support that aids pet owners in perceiving potential stressors as less threatening [ 47 ]. For example, a recent 2021 study found that emotional comfort derived from pets is associated with mental wellbeing (i.e., self-esteem) at moderate and high levels of victimization but not low levels [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These forms of childhood adversity typically involve less perceived threats when compared to direct forms of victimization, such as exposure to intimate partner violence or physical abuse. Indeed, positive human–animal interactions are hypothesized to promote wellbeing by buffering stress both prior to and after activation of the stress response system [ 45 , 46 ] and by providing socioemotional support that aids pet owners in perceiving potential stressors as less threatening [ 47 ]. For example, a recent 2021 study found that emotional comfort derived from pets is associated with mental wellbeing (i.e., self-esteem) at moderate and high levels of victimization but not low levels [ 48 ].…”
Section: Discussionmentioning
confidence: 99%